Morphogenetic diversity in DBM-4 accession of jal brahmi - Saran, Parmeshwar L.; Damor, Hiteksha I. (Indian Horticulture, 2021)
Successful restoration of overexploited species depends upon variability, conservation and cultivation. Elite accessions were characterized for quantitative and qualitative traits for sustainable cultivation and industrial uses. The evaluated accessions were having sufficient variability in morphology, herbage yield and chemical content. The accession DBM-5 was showing maximum dry herbage yield (19.88 t h-1y-1) and DBM-4 rich in bacoside-A3 and bacopaside-II. Overall, economic and/or industrial yield was found maximum in accessions DBM-4, therefore, they may be further used in crop improvement program as valuable selection.